2016
DOI: 10.1080/23746149.2016.1144482
|View full text |Cite
|
Sign up to set email alerts
|

Conical intersections for light and matter waves

Abstract: We review the design, theory, and applications of two dimensional periodic lattices hosting conical intersections in their energy-momentum spectrum. The best known example is the Dirac cone, where propagation is governed by an effective Dirac equation, with electron spin replaced by a "fermionic" half-integer pseudospin. However, in many systems such as metamaterials, modal symmetries result in the formation of higher order conical intersections with integer or "bosonic" pseudospin. The ability to engineer lat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 100 publications
1
30
0
Order By: Relevance
“…where the integral is again taken similarly to Eq. (8). For the spectrum (2), we find [30] w 2 = 0, |sk y | < |m|…”
Section: Our Continuum Model Consists Of a 2d Non-hermitianmentioning
confidence: 99%
See 2 more Smart Citations
“…where the integral is again taken similarly to Eq. (8). For the spectrum (2), we find [30] w 2 = 0, |sk y | < |m|…”
Section: Our Continuum Model Consists Of a 2d Non-hermitianmentioning
confidence: 99%
“…k ∈ π a [−1, 1] becomes a parameter and the winding numbers of each domain are calculated over the 1D Brillouin zone defined by k ⊥ ∈ 2π a √ 3 (−1, 1) using Eqs. (8) and (10) for the field (S4) (see also Section I above). Figure S5 shows k-distributions of the direction angle Re φ and the phase Arg B of the B-field (S4), as well as the corresponding winding numbers w 1 (k ) and w 2 (k ) for γ = 0.4.…”
Section: A Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…This provides a practical method for using all-dielectric photonic structures to realize NZ index media, which have numerous exotic capabilities such as geometry-insensitive wave-guiding [7]. Although the type of band-crossing point utilized in these schemes [8][9][10][11][12][13] is sometimes called "Dirac-like", due to the conical dispersion, it is not actually described by a Dirac Hamiltonian, as evidenced by the fact that the cone is attached to an inseparable flat band [14,15]. The underlying photonic crystals in these studies are Tsymmetric, and so are the effective media, which have NZ refractive index but no magneto-optical activity.…”
mentioning
confidence: 99%
“…It is also found that the nonlinear optical conductivity of graphene would topologically be enhanced in the presence of spin-orbit coupling [38][39][40]. Inspired by these properties of graphene, there is a growing interest in studying similar structures for potential use in nanoelectronics [41].…”
Section: Introductionmentioning
confidence: 99%